Formação de professores de línguas e o letramento digital: o uso das TDICs no contexto de graduação - Bárbara Luíza da Silva Andrade (2021)
With the digital technologies of information and communication gradually more present in the daily life of an increasing portion of the population, it is necessary to reflect on the impact of the training of language teachers for digital literacy since it is necessary that teachers are able not only to use such technologies informally, but also with clear educational purposes. Thus, this work aims to get to know the profile of undergraduate students in the course in Languages, in order to investigate what the perception of these new teachers is about subjects such as digital literacy and multiliteracy, in addition to their perceptions about their levels of digital literacy. In addition, the specific objectives were: to identify events of use of ICTs mentioned by the participants; to verify possible relations between the use of ICTs in the moments before graduation and the appropriation of digital technologies; verify the participants' perception of their own training, with regard to their preparation to deal with the contemporary technological context; identify the gaps reported by the participants and point out indicators that expose their perception of their degrees of digital literacy. In order to achieve these objectives, data generation took place through a questionnaire and a technobiography with undergraduates from courses in Languages from public Universities in the State of Minas Gerais. Technobiography is an autobiography that aims to help us understand the transitions, changes and life practices of users with technologies (BARTON; LEE, 2013). The questionnaire attempted to obtain more precise answers about the participants' perception of their levels of Digital Literacy. The questionnaire was semi-structured and included questions whose answers should be given on a linear scale. The technobiographic writings and questionnaires of the 14 participants were analyzed in a qualitative interpretative manner (Moita Lopes, 1994) and related to the Digital Literacy Global Framework table from Unesco (2018), which provided the necessary indicators to ascertain the perception of the students about their Digital Literacy levels. From the analysis of technobiographies and questionnaires, I found that participants recognize the need to study and include ICTs more in higher education and in basic education. Furthermore, most participants believe that the use, or lack of use, of digital technologies in their basic education has interfered with their current technological knowledge. Participants also admit that there are gaps in undergraduate courses with regard to the study and application of ICTs. I also noticed that, despite the difficulties encountered by the research participants, most of them believe that they are capable of teaching in the contemporary technological context.